Bstan paʼi chos sruṅ rnams la mchod gtor ʼbul tshul phrin las lhun grub bźugs so (T.G. Dhongthog, 1977)
Rituals for the propitation of various protective deities, largely of the Sakyapa tradition of Tibetan Lamaism.